Designing plasmonic gratings with transformation optics - Kraft,M; Luo,Y; Maier,SA; Pendry,JB (Physical Review X, 2015)
Plasmonic gratings that support both localized and propagating plasmons have wide applications in solar cells and optical biosensing. In this paper, we report on a most unusual grating designed to capture light efficiently into surface plasmons and concentrate their energy at hot spots where the field is resonantly enhanced. The dispersion of the surface plasmons shows degeneracy points at k=0, where, despite a strongly modulated grating, hidden symmetries forbid hybridization of plasmons traveling in opposite directions.